Biogeography, Time and Place: Distributions, Barriers and Islands - Renema, Willem (Topics in Geobiology, 2007)
Biogeography considers the distribution of biological units over a wide range of scales. The units range from genotypes, populations and species to families and higher taxa. Processes can be local, such as the isolation on islands due to sea-level fluctuations, or large-scale tectonic processes that separates continents and creates oceans. In all processes time is an important factor and by combining data on recent patterns with paleontological data the understanding of the distribution of extant taxa can be improved. This volume focuses on speciation due to isolation in island-like settings, and the evolution of large-scale diversity as the result of origination, maintenance and extinction.